UJI AKTIVITAS ANTIBAKTERI SEDIAAN OBAT KUMUR KOMBINASI EKSTRAK ETANOL BUNGA CENGKEH (Syzygium aromaticum) DAN KULIT JERUK LEMON (Citrus limon) TERHADAP BAKTERI Streptococcus mutans DAN Streptococcus viridans PENYEBAB KARIES GIGI DAN BAU MULUT - Harahap, Nina Irmayanti; sari, rika puspita; Harnis, Zola Efa (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2023)
Dental caries is an infectious disease and is a process of progressive demineralization of the hard tissue surface of the crown and tooth roots caused by bacterial activity. microorganisms in the mouth. Plaque inhibition can be done with anti-microbial agents to suppress the activity of bacteria such as Streptococcus mutans. Streptococcus mutans is a cariogenic bacterium that causes cavities and is the most dominant in dental plaque. These bacteria can convert sucrose into lactic acid so that it can cause tooth demineralization (Haniyah, 2019). Lemon peel (Citrus limon) is known as an antibacterial ingredient. To facilitate the use of lemon orange peel extract, namely by making it into mouthwash preparations. Mouthwash is a solution that contains antibacterial substances to reduce the number of microorganisms in the mouth, is used as an oral rinse, and is easy to use (Ririn et al., 2019). Research using clove flower extract and lemon peel as antibacterial against Streptococcus mutans and Streptococcus viridans made in mouthwash preparations is still limited, therefore researchers are interested in conducting further research with the title test of antibacterial activity in mouthwash preparations combination of clove flower ethanol extract (Syzygium aromaticum) and lemon peel (Citrus limon) in inhibiting the growth of Streptococcus mutans and Streptococus viridans bacteria that cause bad breath can be formulated into mouthwash preparations and meet the evaluation test requirements for mouthwash preparations and the average diameter of the largest inhibition zone is 12, 31 mm for Streptococcus mutans at a concentration of 2%:0.5% and for Streptococcus viridans at a concentration of 2%:0.5%, namely 11.31.